Interactions and temporal changes in drivers of Urban Water Ecological Carrying Capacity in cities of Hubei Province, China reflect economic, innovation and policy environments - Qimeng Yue; Kate Heal; Zhanjie Li; Jingshan Yu; Xiaolei Yao; Hu Xu; Shugao Xu; Shuang Li; Tong Sun; Zhiyang Yang; Haotian Zhang (Ecological Indicators, 2025)
The Urban Water Ecological Carrying Capacity (UWECC) is a complex, integrated system influenced by water resources, environment, ecology, and socio-economic factors, and is closely linked to high-quality development (HD). Previous studies of UWECC have primarily focused on regional UWECC levels, with limited quantitative exploration of internal system interactions and their impact on the evolution of UWECC. This research constructed a comprehensive UWECC evaluation system using the Driver-Pressure-State-Impact-Response-High quality development (DPSIRHD) framework and applied it to the 16 prefectural-level cities in Hubei Province, China. Dynamic interactions among the urban water ecosystems (UWE) and HD criterion layers were investigated with a panel vector autoregression (PVAR) model and the driving mechanisms of UWECC evolution determined through multiscale geographically weighted regression (MGWR) and Optimal Parameters-based Geographical Detector (OPGD) models. A general upward trend in UWECC performance from 2010 to 2021 was identified in the study cities, marked by four distinct growth periods. The analyses highlighted the centrality of the pressure criterion layer within the UWE system and the intricate interrelations within the HD system, with the criterion layers of driver, response, and new quality productive forces exhibiting significant explanatory power across the interactions between the two systems. The drivers of UWECC performance varied during the study time period, reflecting changing economic, innovation, and policy-driven influences. This research supports sustainable urban water management by highlighting data priorities for more precise UWECC assessments. The methodologies are applicable beyond the study cities and China, serving as a reference for future complex systems research in diverse geographies.